Link between capacity for current production and syntrophic growth in Geobacter species - Rotaru, Amelia-Elena; Woodard, Trevor L.; Nevin, Kelly P.; Lovley, Derek R. (Frontiers in Microbiology, 2015)
Electrodes are unnatural electron acceptors, and it is yet unknown how some Geobacter species evolved to use electrodes as terminal electron acceptors. Analysis of different Geobacter species revealed that they varied in their capacity for current production. G. metallireducens and G. hydrogenophilus generated high current densities (ca. 0.05 mA/cm2), comparable to G. sulfurreducens. G. bremensis, G. chapellei, G. humireducens, and G. uranireducens, produced much lower currents (ca. 0.05 mA/cm2) and G. bemidjiensis was previously found to not produce current. There was no correspondence between the effectiveness of current generation and Fe(III) oxide reduction rates. Some high-current-density strains (G. metallireducens and G. hydrogenophilus) reduced Fe(III)-oxides as fast as some low-current-density strains (G. bremensis, G. humireducens, and G. uranireducens) whereas other low-current-density strains (G. bemidjiensis and G. chapellei) reduced Fe(III) oxide as slowly as G. sulfurreducens, a high-current-density strain. However, there was a correspondence between the ability to produce higher currents and the ability to grow syntrophically. G. hydrogenophilius was found to grow in co-culture with Methanosarcina barkeri, which is capable of direct interspecies electron transfer (DIET), but not with Methanospirillium hungatei capable only of H2 or formate transfer. Conductive granular activated carbon (GAC) stimulated metabolism of the G. hydrogenophilus - M. barkeri co-culture, consistent with electron exchange via DIET. These findings, coupled with the previous finding that G. metallireducens and G. sulfurreducens are also capable of DIET, suggest that evolution to optimize DIET has fortuitiously conferred the capability for high-density current production to some Geobacter species.